Bachelor of Computer Science with Honours (Information Systems) - Universiti Malaysia Sarawak, Faculty of Computer Science and Information Technology (Universiti Malaysia Sarawak (UNIMAS), 2022)
Sijil Ijazah Sarjana Muda (Sistem Maklumat) Fakulti Sains Komputer dan Teknologi Maklumat tahun 2022 bagi 41 orang pelajar.